Pandemic Pivoting: The Use of Home Wi-Fi Accounts and Fast-Food Parking Lots for Teachers’ Internet Connectivity - Trina Harlow, Trina; Yang Yang, Yang; Ackermann, Sarah; Dobberstein, Beth; Reeker, Bob; Needles, Tim (Informa UK Limited, 2023)
Many people and organizations worldwide are still trying to gain access to internet services (Buechner, 2020). The quest for the internet is ongoing, just as electricity was once a privilege when it was first invented and made available mainly to only scientists and engineers, then to people of financial means in primarily urban areas (Southern Oral History Program, n.d.), and continues to be a struggle even today in many parts of the world (Odarno, 2017). Thus, the development and implementation of the ever-morphing internet also continually changes. In early 2020, education was caught off guard by the COVID-19 pandemic. As a result, American education’s need for accessible, reliable internet services for all teachers and students became a prominent concern. In this second part of the National Art Education Association’s Public Policy and Arts Administration Special Interest Group 2020 Device and Internet Accessibility Study, various internet complexities of U.S. school art teachers during hybrid and remote teaching will be discussed.